التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية في العمل مع الحالات الفردية - رشوان، رحاب محمد عبدالسلام Rashwan, Rehab Mohammed Abdulsalam (جامعة الفيوم - كلية الخدمة الاجتماعية, 2022)
استهدفت الدراسة التعرف على مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية في العمل مع الحالات الفردية، وتحقق هذا الهدف من خلال الإجابة على التساؤل الرئيسي للدراسة المتمثل في: ما مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية في العمل مع الحالات الفردية؟ والإجابة على التساؤلات الفرعية التالية: ما مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية في العمل مع العملاء؟ ما مع مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية طبقا لوظيفة المؤسسة؟ ما مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية طبقا للظروف البيئية التي يعيش فيها العميل؟ واشتملت الدراسة على مفهوم قيم ممارسة الخدمة الاجتماعية والممارسة المهنية، واعتمدت الباحثة في إجراء الدراسة على استبيان مطبق على الأخصائيين الاجتماعيين العاملين بمكاتب الخدمة الاجتماعية المدرسية بمحافظة الفيوم، واستمارة مطبقة على عينة عشوائية من الطلاب المستفيدين من الخدمات واستخدمت المسح الشامل للأخصائيين الاجتماعيين العاملين بمكاتب الخدمة الاجتماعية المدرسية بمحافظة الفيوم وعددهم (32) مفردة، واستخدمت أيضا المسح الاجتماعي بالعينة من الطلاب المستفيدين من الخدمات المقدمة من الأخصائي الاجتماعي في المدارس وعددهم (87) مفردة وكان من أهم نتائج الدراسة فيما يتعلق بالإجابة على التساؤل الأول؛ مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية في العمل مع العملاء، حيث أكدت نتائج الدراسة على تقدير العميل لعمل الأخصائي الاجتماعي، وتعاون العميل مع الأخصائي الاجتماعي والمؤسسة، ثم يليها التزام العميل بالقواعد والمسئوليات، وما يتعلق بالتساؤل الثاني؛ مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية طبقا لوظيفة المؤسسة؟ حيث أكدت نتائج الدراسة على توافر إمكانيات المؤسسة، ووجود لوائح المؤسسة التي تساعد على الالتزام المهني، واهتمام المؤسسة بالأشراف والمتابعة وما يتعلق بالتساؤل الثالث؛ مدى التزام الأخصائي الاجتماعي بتطبيق قيم الممارسة المهنية طبقا للظروف البيئية التي يعيش فيها العميل؟ حيث أكد الأخصائيين الاجتماعيين على التنشئة الاجتماعية السليمة، وتوافر الظروف المعيشية الجيدة، وتوافر الموارد والإمكانيات، وسيادة العدالة وتكافؤ الفرص في المجتمع. The study aimed to identify the extent of the social worker's commitment to applying the values of professional practice in working with individual cases, and this goal was achieved by answering the main question of the study represented in:What is the extent of the social worker's commitment to applying the values of professional practice in working with individual cases? And the answer to the following sub-questions: What is the extent of the social worker's commitment to applying the values of professional practice in working with clients? What is the extent of the social worker's commitment to applying the values of professional practice according to the function of the institution What is the extent of the social worker's commitment to applying the values of professional practice according to the environmental conditions in which the client lives? The study included the concept of values and professional practice. In conducting the study, the researcher relied on a questionnaire applied to social workers working in school social service offices in Fayoum governorate, and a questionnaire applied to a random sample of students benefiting from services, and used a comprehensive survey of social workers working in school social service offices in Fayoum governorate. Fayoum, their number (32) singles, and a social survey of the sample of students benefiting from services provided by the social worker in schools was also used, and their number was (87) singles. One of the most important results of the study with regard to answering the first question; the extent of the social worker’s commitment to applying the values of professional practice in working with clients. The results of the study confirmed the client’s appreciation of the social worker’s work, and the client’s cooperation with the social worker and the institution, followed by the client’s commitment to the rules and responsibilities, and what is related to the second question; The extent of the social worker's commitment to applying the values of professional practice according to the function of the institution? The results of the study confirmed the availability of the institution’s capabilities, the existence of the institution’s regulations that help professional commitment, the institution’s interest in supervision and follow-up, and what is related to the third question; To what extent is the social worker committed to applying the values of professional practice according to the environmental conditions in which the client lives? Where social specialists emphasized sound social upbringing, good living conditions, resources and capabilities, the rule of justice and equal opportunities in society.
Keywords: الأخصائيون الاجتماعيون -- الأخلاقيات المهنية -- الخدمة الاجتماعية -- المشكلات الاجتماعية -- القيم المجتمعية